Is the Solar Wind Electron Strahl a Seed Population for the Earth’s Electron Radiation Belt? - Borovsky, Joseph E.; Runov, Andrei (Frontiers in Astronomy and Space Sciences, 2022)
(1) Since the outer electron radiation belt is lost on occasion, the radiation belt needs seed electrons to rebuild. (2) The clear candidate for that seed population is energetic substorm-injected electrons in the dipolar magnetosphere. (3) The energetic substorm-injected electrons in the dipole come from the suprathermal electron population in the magnetotail plasma sheet, delivered by substorms. Scenario (1)-(3) begs the question: Where do these magnetotail suprathermal electrons come from? We are hypothesizing that one source (perhaps the dominant source) is the energetic field-aligned electron strahl in the solar wind, which are electrons fresh from the solar corona.